Ibero American Science and Technology Education Consortium (ISTEC): New Challenges in Collaborative Work - De Giusti, Marisa Raquel (2012)
The Ibero-American Science and Technology Education Consortium (ISTEC) is a non-profit organization comprised of educational, research, industrial, and multilateral organizations throughout the Americas and the Iberian Peninsula. The Consortium was established in 1990 to foster scientific, engineering, and technology education, joint international research and development efforts among its members, and to provide a cost-effective vehicle for the application and transfer of technology. After twenty years, ISTEC has established a presence in the region, but it also has experienced problems to interact with different cultures and interests. During 2010 it suffered important changes in its organization and big efforts were realized to accomplish new goals and to share worldwide expertise, to facilitate distributed problem solving, creating the local critical mass needed for the development of regional projects in areas such as: continuing education, libraries and repositories, globalization of the culture of quality and accreditation standards, R&D, intellectual property development, capital acquisition, and social responsibility, among others. ISTEC continues to be dedicated to the improvement of Science, Engineering, Technology, Math education, R&D, and Entrepreneurship. The Consortium will foster technology transfer and the development of social and business entrepreneurs through the implementation of a global network that pretends to reach other countries in the world creating clusters of businesses and institutions that share common interest, assisting in the establishment of strategic alliances/joint ventures, and the promotion of collaborative partnerships in general.